Diagnosis, prevention and treatment of central nervous system involvement in peripheral t-cell lymphomas. (November 2021) - Zing, Natalia; Fischer, Thais; Federico, Massimo; Chiattone, Carlos; Ferreri, Andrés J.M.
Graphical abstract: Highlights: CNS involvement, at initial diagnosis or relapse, is uncommon in T-cell lymphomas. CNS prophylaxis could reduce high mortality rates of some high-risk entities. Critical review of literature allows us to identify these high-risk T-cell lymphomas. High-dose methotrexate is used as prophylaxis, but supporting evidence is uncertain. Prognosis of CNS T-cell lymphomas is poor; novel therapies are urgently needed. Abstract: Non-Hodgkin lymphomas with T-cell immunophenotype encompass a heterogeneous group of infrequent neoplasms that follow variable clinical courses but prevalently include aggressive behavior and high mortality rates. The involvement of the central nervous system (CNS) is an uncommon event in T-cell lymphomas, with wide variability among the different disease entities. CNS can be affected either at initial diagnosis or at recurrence, and both forms are considered "secondary CNS T-cell lymphoma". Given the low incidence of secondary CNS T-cell lymphoma, related literature is sparse, contradictory, and primarily constituted by small case series and single case reports. However, reported studies uniformly suggest high mortality rates related to this event. Therefore, to improve our ability to identify high-risk patients and offer them successful CNS prophylaxis or timely and effective treatment once the event has occurred may prevent CNS-related T-cell lymphomas deaths. For example, some entities like aggressive adult T-cell leukemia/lymphoma, extranodal natural killer/T-cell lymphoma, and other peripheral T-cell lymphomas with involvement of two or more extranodal organs are prone to CNS dissemination and should be considered for personalized CNS prophylaxis. The level of evidence suggesting an increased risk of CNS recurrence for other T-cell lymphomas and for other risk factors is lower. Published case series show that, following the example of aggressive B-cell lymphomas, patients with T-cell lymphomas and putative increased CNS risk receive different forms of prophylaxis, mostly methotrexate and cytarabine delivered by intrathecal and/or intravenous routes, with varied success. To date, achievements in the treatment of CNS involvement in patients with aggressive B-cell lymphoma were not replicated in secondary CNS T-cell lymphomas, and identification of effective therapies remains an urgent research target. This review is focused on clinical findings, diagnosis, treatment, and prognosis of patients with T-cell lymphoma experiencing CNS dissemination either at presentation or relapse. It aims to provide logical and, oftentimes, evidence-based answers to the most common questions on the most probable risk factors to CNS involvement in patients with T-cell lymphoma, the indications and strategies to prevent this life-threating event, and the management of patients with CNS disease.